An investigation of the pharmacological applications used for the Ancient Egyptian systemic model 'ra-ib' compared with modern Traditional Chinese Medicine. (30th January 2021) - Russell, Jonny; Sun, Mengmeng; Liang, Wen; He, Min; Schroën, Yan; Zou, Wenjun; Pommerening, Tanja; Wang, Mei
Abstract: Ethnopharmacological relevance: Ancient Egyptian texts only offer glimpses into their conceptual understandings of the inner-body and illness manifestation. Explanations of how prescribed materia medica were believed to work are rare and obscure, often resulting in modern approximations for ancient terminology such as ' ra-ib '—an ancient Egyptian classification predominantly translated as 'stomach'—leading to misunderstandings of historical texts, and therefore their use of pharmacology. Aim of the study: To investigate the ra-ib and the explanatory models of illness from the Egyptian perspective, and to explore the link between these and the prescribed selection of materia medica . To then compare the conceptual mechanics of these treatment strategies with those of another non-Western tradition—namely Traditional Chinese Medicine (TCM)—to provide further insight into potential conceptual frameworks. Materials and methods: We conducted a case study of a unit of Ancient Egyptian texts focusing on the ra-ib . Totalling 34 prescriptions, the first stage lexicographically analysed the texts using cognitive linguistic and translation theories to produce our new understanding. This enabled our comparison of the mechanics of materia medica usage within these texts with those found in TCM outlined by the Pharmacopoeia of the Peoples Republic of Pharmacopeia of the People's Republic of China 2015 for the relevant ingredients. Results: the study demonstrated that—rather than denoting the organ 'stomach'– ra-ib instead constitutes a system running from the mouth, downward to the anus. This is best translated as 'inner thoroughfare', and changes the way in which we attempt to understand potential motivations in the selection of ingredients. By exploring common themes in the use of eleven securely translated ingredients from the Egyptian corpus and the Pharmacopoeia of the People's Republic of China —representing a modern traditional system which understands the body via a series of interconnected systems—we were able to highlight certain themes which might be 'universal' to system-based traditions; this provided new insights into the Egyptian motivations for treatment selection. Conclusions: Having gained the ancient view of the body and illness, cultural comparisons are important for providing further potential insights and clarifications of a discontinued historical healing tradition. The new understanding of the ra-ib from our study greatly changes the way in which we understand the dynamics of Egyptian ethnopharmacological source material from this period. Graphical abstract: Image 1